The Effect of KWL (Know, Want to Know, Learned) Strategy on Improving Reading Comprehension Skills in Intellecual Disability Students - Rusdianti, Fahriyana; Sunandar, Asep; Dewantoro, Dimas Arif (Proceedings Series of Educational Studies, 2024)
This study aims to improve the reading comprehension skills of students with intellectual disability by using the KWL (Know, Want to Know, Learned) reading strategy. This research used quantitative methods with a one group pre-test post-test research design. The research subjects consisted of 5 middly intellectual disability students in grades V-VIII. The research instrument was a test of 20-questions with indicators that measure the ability to understand words, sentences and capture explicit information from reading texts. The treatment was given 4 times. The results showed an increase in post-test scores when compared with pre-test scores. The pre-test average score showed 45 with very low criteria, while the post-test average score shows 72 with good criteria. The hypothesis was then tested using the Wilcoxon test and obtained a value of 0.039 < 0.05. Based on the result of this study, KWL strategy can hone students’ skills in remembering, speaking, reading, and understanding. In addiotion, KWL stratgey also increases student motivation and participation in learning activities. So it can be concluded that the reading comprehension ability of intellectual disability students in grades V-VIII through the application of the KWL strategy has increased. Keywords: Intellectual disability, reading comprehension, KWL strategy